Stability Analysis of HIV/AIDS Model with Educated Subpopulation - Habibah, Ummu (CAUCHY, 2021)
We had constructed mathematical model of HIV/AIDS with seven compartments. There were two different stages of infection and susceptible subpopulations. Two stages in infection subpopulation were an HIV-positive with consuming ARV such that this subpopulation can survive longer and an HIV-positive not consuming ARV.  The susceptible subpopulation was divided into two, uneducated and educated susceptible subpopulations.  The transmission coefficients from educated and uneducated subpopulations to infection stages were  where  ((  and ) (  and )) In this paper, we consider the case of  and  were zero.  We investigated local stability of the model solutions according to the basic reproduction number as a threshold of disease transmission. The disease-free and endemic equilibrium points were locally asymptotically stable when  and  respectively. To support the analytical results, numerical simulation was conducted.